Do patients on oral chemotherapy have sufficient knowledge for optimal adherence? A mixed methods study. (25th November 2015) - Arber, A.; Odelius, A.; Williams, P.; Lemanska, A.; Faithfull, S.
Abstract : A new treatment paradigm has emerged with many patients now receiving oral chemotherapy (OC) as first‐line treatment for cancer. Treatment with OC has resulted in reduced hospital costs, more autonomy for patients but with added responsibilities for patient self‐management. Little is known about patient's knowledge following patient education to enable optimal adherence with OC. A mixed methods study was carried out using a self‐report questionnaire to patients on OC for multiple myeloma (MM) followed by semi‐structured interviews with patients at home. Analysis identifies high rates of adherence (92.2%) with OC for MM. However, statistically significant knowledge deficits were identified, which were related to patient ethnicity and to gender. There is the potential for non‐intentional non‐adherence with OC due to deficits in knowledge of OC. Support at home needs to include primary care practitioners such as GPs, practice nurses and pharmacists so that timely support is easily accessible especially in the early phase of treatment.